Pelatihan Pembuatan Zat Pengatur Tumbuh Alami dan Pupuk Organik Cair Kepada Petani Nilam Di Desa Nggawia Kabupaten Tojo Una-una - Kamelia Dwi Jayanti; Yulinda Tanari (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This activity aims to develop partners' knowledge and skills regarding liquid organic fertilizers (LOF) and growth regulators (GR) through counseling and training in the form of technical assistance and guidance. Implementation methods included extension, manufacture of LOF and GR, application to plants, and evaluation. The target of the implementation of this service was patchouli farmers in Nggawia Village. The initial evaluation instrument was in the form of a questionnaire, while the final evaluation was only in the form of questions and answers during the implementation of the activity. In addition, a simple experiment was carried out on patchouli plants to determine the effectiveness of LOF and GR. The questionnaire, discussion, and experiment results were described based on the data obtained and the experimental parameters. This activity showed that the training on making LOF and GR has succeeded in increasing the knowledge and skills of farmers in Nggawia Village, West Tojo District, Tojo Una-Una Regency. The average plant height and number of shoots applied by POC and POC coconut water was higher than control, and only POC or ZPT was used singly.